Tag it: Issue 4/Apr 2014 Band of Heroes - Universiti Malaysia Sarawak, Centre for Information Technology Development & Services (Universiti Malaysia Sarawak, (UNIMAS), 2014)
In this issue of Tag-it, we provide a glimpse into our “Band of Heroes”. The people behind some of the ICT advances in UNIMAS. We pay tribute to the tireless un-sung heroes working behind the scenes and providing essential services that help drive the inner gears of a university.